Effects of Lime (Citrus aurantifolia Swingle) Peel Extract Addition to Periodontal Dressing on the Number of Blood Vessels in the Gingival Wound Healing Process - Fauzia, Malianawati; Oktaviana, Savira Pratista (Journal of Dentistry Indonesia, 2022)
Background: Periodontal dressings that are currently available can only protect wounds from mechanical trauma, but have no ability to accelerate wound healing. Lime (Citrus aurantifolia Swingle) peel extract added to periodontal dressing contains flavonoids which can stimulate the formation of new blood vessels, thus accelerating the healing process. Objective: To determine the effects of adding lime (Citrus aurantifolia Swingle) peel extract to periodontal dressing on the number of blood vessels in the gingival wound healing process. Methods: 32 rabbits with 2 mm wound made on the gingiva were divided into 8 groups. For the control groups of K1(n=4) and K2(n=4) periodontal dressings were applied without the addition of lime peel extract. Meanwhile, the treatment groups P1(n=4) and P4(n=4), P2 (n=4) and P5(n=4), and P3(n=4) and P6(n=4), 5%, 10%, and 15% lime peel extract, respectively, were added to the periodontal dressing. Groups K1, P1, P2, and P3 were scarified after 3 days, whereas groups K2, P4, P5, and P6 were scarified after 5 days. Histological observations of tissue by Hematoxylin Eosin (HE) staining were carried out to count the number of blood vessels. Result: The results of the statistical tests show that group P5 had the highest number of new blood vessels. Conclusion: The addition of lime peel extract to periodontal dressing can increase the number of blood vessels in the gingival wound healing process.